Effects of physical activity on eating disorder tendencies in college students: the chain-mediated effects of trait positivity and physical self-esteem - Jiang, Yong; Meng, XiangZheng (Frontiers in Psychology, 2025)
AimThis study aimed to explore the influence mechanism of physical activity on eating disorder tendencies in college students and analyze the chain-mediated role of trait positivity and physical self-esteem.MethodsUsing the Physical Activity Rating Scale, Eating Disorder Tendency Scale, Trait Positivity Scale, and Physical Self-Esteem Scale, 550 college students from four universities in Northeast China were surveyed.Results(1) Physical activity was significantly negatively correlated with eating disorder tendencies in college students (r = −0.361; p < 0.01); trait positivity was significantly negatively correlated with eating disorder tendencies in college students (r = −0.275; p < 0.01); physical self-esteem was significantly negatively correlated with eating disorder tendencies in college students (r = −0.436; p < 0.01); physical activity was significantly positively correlated with trait positivity (r = 0.223; p < 0.01); physical activity was significantly positively correlated with physical self-esteem (r = 0.371; p < 0.01); trait positivity was significantly positively correlated with physical self-esteem (r = 0.433; p < 0.01). (2) Physical activity could negatively predict eating disorder tendencies in college students, with a direct effect of −0.0202. (3) In the association between physical activity and eating disorder tendencies in college students, trait positivity and physical self-esteem could exert both separate mediating effects and a chain-mediated effect, with effect values accounting for 4.02, 17.23, and 4.76% of the total effect, respectively.ConclusionPhysical activity is associated with eating disorder tendencies in college students, and this association occurs both through the mediating roles of trait positivity and physical self-esteem and through their chain-mediated effect.